STRATEGI PENURUNAN RISIKO KEGAGALAN IMPLEMENTASI PENGURANGAN EMISI DARI DEFORESTASI DAN DEGRADASI HUTAN: STUDI KASUS DI MERANG, PROVINSI SUMATERA SELATAN - Deden Djaenudin; Elvida Yosefi Suryandari; Aneka Prawesti Suka (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2015)
Indonesia is still in the preparation phase of REDD+ implementation, with various constraints due to uncertainties. These uncertainties lead to failure risk of the implementation of REDD+. This study aims to provide some alternative strategies to alleviate the risk of failure. The study conducted in Merang, Musi Banyuasin, South Sumatra Province, by interviewing key persons and assessing the impact of the risks by using Voluntary Carbon Standard (VCS). This study scrutinized the source of uncertainties, risks and their impact on the project performance. Based on the possibility of their occurrences, sources of uncertainties associated with issues are: a) encroachment activities, b) settlement needs, c) numberof loggers, d) land tenure, and e) forest fires. Based on the VCS assessment, the levelof risk that occurred in Merang is in medium level and the impact of REDD+ implementation is not feasible. The risk reduction strategies can be done by providing buffer area, changes in land status as a protected area, and reduce land conflicts through improved governance. The issuesof non-permanence can be avoided through adoption of disincentives for failed developers, applying an appropriate adaptive payment scheme, optimizing the utilization of co-benefits and providing an effective and efficient funding distribution mechanism.